(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Evaluation of treatment results of endometrioma in the ovary by laparoscopy. Subjects and methods: A retrospective cross-sectional description of 81 patients with endometriosis cysts operated at Nghe An Obstetrics and Pediatrics Hospital. Results: Dysmenorrhea was the main reason for patients to go to the doctor (35.8%); Laparoscopy correctly diagnosed 96.3%; The rate of laparoscopic surgery is 87.7%; The rate of cyst removal from endometriosis ± de-adhesion is 87.7%; Laparoscopic surgery has a faster surgery time than the open surgery group (61.2 ± 17.0 minutes versus 82.0 ± 23.8 minutes), p < 0.05. Laparoscopy has a faster post-operative transit time than the open surgery group (25.0 ± 7.0 hours versus 30.4 ± 10.6 hours), p < 0.05; The rate of complications was 6.2%, mainly after open surgery. Conclusion: Laparoscopy is the main treatment method. Compared with ultrasound, laparoscopy more accurately diagnose endometrioma. Laparoscopy has advantages: shorter surgery time, shorter postoperative transit time and fewer complications